(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
Objective: This study analyzed how Brazilian research on compliance is configured in the Spell® database. Method: Bibliometric study using, for data collection, the term “compliance” in the title of the articles, considering all the years of the base until 2021. Results: The search yielded 19 articles, 80% published in the last three years – from 2018 to 2020. The authors of the publications come from different universities, and the quality of the scientific articles is high, considering that Qualis/Capes rates approximately 70% of them in strata A3 and A4. Benefits of implementing a compliance program in companies were observed, such as combating and preventing money laundering, good market reputation, risk mitigating with fraud, corruption, and financial losses, transparency, and credibility of public and private entities. Contributions: This research is a stimulus to researchers for a theoretical-empirical deepening on compliance and to other readers (managers, entrepreneurs, and executives), provides a conceptual regulatory overview, and presents compliance benefits for companies. In conclusion, the topic is still little explored theoretically and empirically in academia, which implies that there is still a vast field of empirical research to be explored in future studies.